Handbook of research on human resources strategies for the new millennial workforce - Ordonez de Pablos, Patricia, 1975-; Tennyson, Robert D. (Hershey, PA : Business Science References, 2017)
'This book is an authoritative reference source for the latest scholarly research on theoretical frameworks and applications for the management of millennials entering the professional realm, focusing on methods and practices to enhance organizational performance and culture'--
Includes bibliographical references (pages 433-511) and index.
Keywords: Personnel management; Generation Y -- Employment